Secret admirer - Roy, Ron, 1940- (Roy, Ron, 1940- A to Z mysteries. Super edition, 2015)
It's Valentine's day in Green Lawn! But Dink, Josh, and Ruth Rose just aren't feeling the love this year. Valentine's Day was so much more fun when they were little. Then they each start getting messages and clues from a secret admirer! Can the kids figure out who wants to be their valentine?